Evaluasi Atas Penerapan Pp 23 Tahun 2018 Pada Kantor Pelayanan Pajak Pratama Kabanjahe - Agus Bandiyono; Rika Permatasari Simarmata (ITB AAS INDONESIA, 2021)
This research was conducted to evaluate the implementation of Government Regulation No. 23/2018 at the Kabanjahe Primary Tax Office and to find out the problems faced in implementing these regulations. The method used in this research is a qualitative method which is carried out by direct interviews with 2 Account Representatives at KPP Pratama Kabanjahe. The results of this study indicate that the implementation of PP 23 of 2018 at KPP Pratama Kabanjahe can be said to be quite effective. This is based on data on taxpayers who pay PPh Final PP 23 which has increased quite significantly. In addition, there was an increase in PPh Final PP 23 deposits throughout 2018 to 2019. Although there was a decrease in the amount of deposits compared to the previous year, this was due to a decrease in rates from 1% to 0.5%. Although the implementation of PP 23 at KPP Pratama has been quite effective, it does not affect the percentage of taxpayers' compliance, especially corporate taxpayers. Meanwhile, the percentage level of non-entrepreneur individual taxpayer compliance has increased from 2016 to 2019, so it can be concluded that this rule is quite effective in increasing the compliance level of individual taxpayers.